2013
DOI: 10.1080/01431161.2013.820365
|View full text |Cite
|
Sign up to set email alerts
|

Intercalibration of DMSP-OLS night-time light data by the invariant region method

Abstract: DMSP-OLS (Defense Meteorological Satellite Program Operational Linescan System) night-time light data can accurately reflect the scope and intensity of human activities. However, the raw data cannot be used directly for temporal analyses due to the lack of inflight calibration. There are three problems that should be addressed in intercalibration. First, because of differences between sensors, the data are not identical even when obtained in the same year. Second, different acquisition times may lead to random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 24 publications
4
118
0
Order By: Relevance
“…Because DMSP/OLS nighttime light data were produced by different satellites and OLS sensors which had no on-board calibration, we could not directly use the multi-year nighttime light to map the statistical energy consumption, due to the lack of continuity and comparability [35,36]. We first preprocessed the nighttime light data, according to the methodology developed by Liu et al (2012) [37].…”
Section: Mapping Statistical Energy Consumption Datamentioning
confidence: 99%
“…Because DMSP/OLS nighttime light data were produced by different satellites and OLS sensors which had no on-board calibration, we could not directly use the multi-year nighttime light to map the statistical energy consumption, due to the lack of continuity and comparability [35,36]. We first preprocessed the nighttime light data, according to the methodology developed by Liu et al (2012) [37].…”
Section: Mapping Statistical Energy Consumption Datamentioning
confidence: 99%
“…These include the invariant region and the quadratic regression method proposed by Elvidge et al [23], the second-order regression and optimal threshold method proposed by Liu et al [24], and a power-law regression method proposed by Wu et al [25]. Although studies based on these calibration methods showed performance improvement after the rectification [24,25], the assumption that the nighttime light remains stable over time in a particular area requires a careful choice of the invariant region manually.…”
Section: −1°mentioning
confidence: 99%
“…The absence of inter-satellite calibration and onboard calibration strongly limits the inter-annual comparability of light intensity represented by the digital number (DN) values. To overcome this limitation, different inter-calibration methods, largely based on an assumption that light intensity in some areas did not change throughout the timeframe of interest, were proposed by researchers [23][24][25]36].…”
Section: Types Of Dmsp/ols Datasetsmentioning
confidence: 99%
“…To resolve the inherent problem of saturation in brightly lit areas, especially urban centers, saturation correction is needed for DMSP-OLS stable light products. A series of saturation correction methods have been proposed so far, and among these the invariant method [30][31][32][33] is widely used and well received. In this paper, the invariant method proposed by Shi et al [31] was used for data processing.…”
Section: Data Collectionmentioning
confidence: 99%